2011
DOI: 10.1371/journal.pone.0021631
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Synthesis of Corticosteroids in the Hippocampus

Abstract: BackgroundBrain synthesis of steroids including sex-steroids is attracting much attention. The endogenous synthesis of corticosteroids in the hippocampus, however, has been doubted because of the inability to detect deoxycorticosterone (DOC) synthase, cytochrome P450(c21).Methodology/Principal FindingsThe expression of P450(c21) was demonstrated using mRNA analysis and immmunogold electron microscopic analysis in the adult male rat hippocampus. DOC production from progesterone (PROG) was demonstrated by metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 51 publications
1
47
0
Order By: Relevance
“…However, 11b-hydroxylase catalyses the conversion of 11-DCC to CCS, and we found a significant level of 11-DCC in the testis (Table II), indicating the possibility of the biosynthesis of CCS via the 11b-hydroxylation of the 11-DCC detected in rat testis. We also observed significant levels of 11-DCC in the brain, suggesting the possibility of CCS biosynthesis in the brain, as previously reported in the hippocampus (33). Recently, neurosteroid glucuronides have been found in mouse brain by LC-MS analysis, and the authors showed the formation of those glucuronides in vitro using a brain homogenate S-9 fraction (34).…”
Section: Discussionsupporting
confidence: 85%
“…However, 11b-hydroxylase catalyses the conversion of 11-DCC to CCS, and we found a significant level of 11-DCC in the testis (Table II), indicating the possibility of the biosynthesis of CCS via the 11b-hydroxylation of the 11-DCC detected in rat testis. We also observed significant levels of 11-DCC in the brain, suggesting the possibility of CCS biosynthesis in the brain, as previously reported in the hippocampus (33). Recently, neurosteroid glucuronides have been found in mouse brain by LC-MS analysis, and the authors showed the formation of those glucuronides in vitro using a brain homogenate S-9 fraction (34).…”
Section: Discussionsupporting
confidence: 85%
“…Note that synaptically localized GR, ER␣ were observed by immunoelectron microscopic analysis (Fig. 6) [16,25]. Under these conditions of weakend LTP by CORT, ER␣ may play significant role due to lower Ca 2+ concentration (may be 5 M).…”
Section: Modulation Of Synaptic Plasticity By Hippocampal Sex Steroidsmentioning
confidence: 88%
“…We have found that even 10 nM CORT is enough to increase the spine density ( Supplementary Fig. S9, see section on supplementary data given at the end of this article; Higo et al 2011).…”
Section: Contribution Of Slow Effects Of Gr To Spine Changes May Be Weakmentioning
confidence: 92%
“…The average concentration of CORT in the hippocampus was 23.7 ng/g wet weight (68.4 nM; nZ3), slightly higher than that in the CSF of intact rats in the awake state (w30 nM). Upon CORT injection into ADX rats, the hippocampal CORT became much higher than that in ADX rats without CORT injection (6.9 nM; Higo et al 2011).…”
Section: Depletion Of Circulating Cort Suppressed the Change Of The Smentioning
confidence: 94%